(untitled) (Impact: Journal of Transformation, 2022)
The purpose of this research was to determine the common challenges faced by the youth as caregivers of those with disabilities and determine ways of overcoming these common challenges that the youth caregivers were facing. This study was conducted at PCEA Kikuyu Youth Church; the target population is youth caregivers, those between 13 and 35 years of age. The main research instruments used were interviews and observation. The research method used was qualitative with a phenomenology approach. Purposive sampling was used, where six respondents who had been caregivers for their family members and students were interviewed and observed. These youth caregivers’ common challenges were established by memoing, then color coding, analyzing and finally interpreting the emerging themes, which were the common challenges as spiritual need, financial need, recreation need, knowledge and skills and shattered goals and dreams. The process of coding and theming common ways of overcoming these challenges were established: pastoral care, prayers, fellowship, financial support, family support, training, outings, breaks, and church and community support.